(untitled) (Research, Society and Development, 2021)
Objective: to know the repercussions of syphilis on pregnancy and the possibility of nursing work. Methodology: Integrative literature review carried out in July 2020 in the VHL, SciELO and PubMed, using the DeCS: nursing care, syphilis, maternal and child health, prenatal care and pregnancy. Original articles in full, in Portuguese, English and Spanish, published between 2015 and 2020, were selected. Results: The 3 selected articles addressed the themes: impact of syphilis on the mother; consequences of vertical transmission for the fetus and/or neonate and possibilities for nursing work. The main repercussions of syphilis for the mother were psychological damage, and for the newborn, the early or late appearance of the infection can result in short or long term sequelae. Faced with this, nursing must act throughout the care process, in educational actions such as promotion, prevention, early diagnosis and treatment. Final Considerations: Syphilis has serious repercussions for the maternal-fetal binomial and, in view of this, nursing has a fundamental role in combating this pathogen, seeking to curb the possible damage caused to maternal and child health as quickly as possible.